Hubungan Pengetahuan dan Sikap dengan Perilaku Buang Air Besar Sembarangan Masyarakat Desa Sumberwaru Kecamatan Banyuputih Kabupaten Situbondo Tahun 2021 - Da’i Maulana Hidayat; I Nyoman Sujaya (Poltekkes Kemenkes Denpasar, 2022)
Basic sanitation is the minimum sanitation to provide healthy environment that meets health requirements and focuses on monitoring various environmental factors affect the degree of human health. One of them is Healthy Latrine. Defecation (defecating) in open areas such as rivers or gardens has become a habit that is often practiced by the community. The habit of open defecation, which results in contamination of drinking water and food sources. The research objective determine whether there was a relationship between knowledge and attitudes the community and the behavior of open defecation in Sumberwaru Village, Banyuputih District, Situbondo Regency. The defecation behavior in Sumberwaru Village, Banyuputih District can be said to be high, namely as many as 1244 families out of 3232 families, the sample of the study was 105 families. This type of research usesmethod cross sectional. Data analysis used the Chi-square test. Results showed that the value of ρ = 0.000, which means that there is a relationship between knowledge and attitude and defecation behavior